Modelling and optimisation of low-indirect land used change biomass supply chains - Ibrahim,D; Giarola,S; Panoutsou,C; Diaz-Chavez,R; Shah,N (Bioresource Technology Reports, 2024)
Biofuels derived from biomass feedstocks produced following the implementation of measures that avoid indirect land used change (ILUC) have the potential of reducing dependency on fossil-based fuels without competing with food value chain. This work develops a model- and optimisation-based methodologies that address challenges related to the production of low-ILUC biomass feedstocks. Case studies investigated include planning of Iow-ILUC biomass feedstock production, biomethane production using low-ILUC biomass feedstocks, integrated production of first generation (1G) and second generation (2G) bioethanol using Miscanthus, and production of hydrotreated vegetable oil (HVO) using castor seeds. Analysis of results show that farmers interested in these models are recommended to sell low-ILUC biomass such as soybean, wheat and brassica above the breakeven price to avoid losses. The estimated selling price for the three crops are 362 €/t, 321 €/t and 381 €/t respectively. To meet the demand of 40,000 t/yr of 2G bioethanol in the UK, approximately 17,094 ha of underutilised land is required. Policy makers should consider options to support alternatives such as retrofitting, and inter-cropping to avoid or mitigate ILUC.